Cambiando los relatos del envejecimiento: las representaciones de la vejez femenina de Emma Thompson en Late night y Buena surte, Leo Grande - Dra. Núria CASADO GUAL,Dra. Maricel ORÓ PIQUERAS (Fonseca, Journal of Communication, 2023)
At the onset of her sixtieth decade, Emma Thompson remains a prolific actress, whilst 'age' has become a more salient trait in her cinematic roles. While in the film Late Night(2019) she depicts a critical moment in the life of a successful late-night talk-show host whose career seems to reach a dead end when she turns sixty, in Good Luck to You, Leo Grande (2022) she presents the personal quest of a recently widowed woman to feel sexual pleasure for the first time in her life.